EFEKTIVITAS PERATURAN DAERAH NOMOR 1 TAHUN 2018 TENTANG PENDIRIAN DAN PENGELOLAAN BADAN USAHA MILIK DESA TERHADAP PERKEMBANGAN BADAN USAHA MILIK DESA DI KABUPATEN KLATEN (BUMDES MEGER NGADEG JEJEG) - Nafisah, Fadwa Nur; Suranto, Suranto (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2020)
This study aims to first, determine the effectiveness of Regional Regulation Number 1 of 2018 concerning the Establishment and Management of Village-Owned Enterprises for the development of village-owned enterprises in Klaten Regency. Second, analyzes the inhibiting factors of the development of village-owned enterprises. The type of research that the author uses in compiling this legal research is descriptive empirical legal research. The approach used is the legislative approach and case approach.The results of this study say that village-owned enterprises in Klaten Regency have not been able to run optimally because there are still many disparities between business entities that have been developed with business entities that are newly formed or growing. The inhibiting factor in the process of forming and developing village-owned enterprises is that there are no rules that clarify the course of village-owned enterprises coupled with the lack of capital owned by village-owned enterprises.